Green Process Innovation and its Impact on Sustainability Performance: The Mediating Role of Green Supply Chain Management in the Food and Beverage Industry - Rafli, Muhammad Raihan; Makiah, Zulpa; Claudia, Meiske; Syahputra, Muhammad Dio; Aisyah, Lisda; Faridah, Rohana (Journal of Entrepreneurship & Business, 2025)
Purpose: The food and beverage sector, which contributes significantly to plastic waste in Indonesia, may reduce its usage of single-use plastics by using green process innovation (GPI). By incorporating economic and environmental goals into the strategic management of supply chain operations, Green Supply Chain Management (GSCM) can propel this. This study aims to evaluate the role of GPI and GSCM in achieving sustainable corporate performance (SP) in Indonesia, especially in the food and beverage industry. Method: Purposive sampling was used to select samples from the food and beverage industry during the 2021-2023 period which resulted in 12 companies as samples. Path analysis was used as a data analysis method in this study. After that, Warp-PLS 8.0 software was used to process the data obtained. Result: The results showed that GPI has a positive and significant influence on SP, and GPI has a positive and considerable influence on GSCM. Meanwhile, GSCM does not influence SP, and GSCM cannot mediate the influence between GPI and SP.